SARS-CoV-2 variants of concern display enhanced intrinsic pathogenic properties and expanded organ tropism in mouse models - Stolp-Rastätter, Bettina; Stern, Marcel; Ambiel, Ina; Hofmann, Katharina; Morath, Katharina; Gallucci, Lara; Cortese, Mirko; Bartenschlager, Ralf; Ruggieri, Alessia; Graw, Frederik; Rudelius, Martina; Keppler, Oliver Till; et al. (Cell reports, 2022)
SARS-CoV-2 variants of concern (VOCs) display enhanced transmissibility and resistance to antibody neutralization. Comparing the early 2020 isolate EU-1 to the VOCs Alpha, Beta, and Gamma in mice transgenic for human ACE2 reveals that VOCs induce a broadened scope of symptoms, expand systemic infection to the gastrointestinal tract, elicit the depletion of natural killer cells, and trigger variant-specific cytokine production patterns. Gamma infections result in accelerated disease progression associated with increased immune activation and inflammation. All four SARS-CoV-2 variants induce pDC depletion in the lungs, paralleled by reduced interferon responses. Remarkably, VOCs also use the murine ACE2 receptor for infection to replicate in the lungs of wild-type animals, which induce cellular and innate immune responses that apparently curtail the spread of overt disease. VOCs thus display distinct intrinsic pathogenic properties with broadened tissue and host range. The enhanced pathogenicity of VOCs and their potential for reverse zoonotic transmission pose challenges to clinical and pandemic management.
Gesehen am 28.03.2022